Prognostic significance of lateral pelvic lymph node dissection for middle-low rectal cancer patients with lateral pelvic lymph node metastasis: a propensity score matching study - Sicheng Zhou; Yujuan Jiang; Wei Pei; Jianwei Liang; Zhixiang Zhou (BMC Cancer, 2022)
Abstract Background There is still controversy regarding the clinical value and significance of lateral pelvic lymph node (LPN) dissection (LPND). The present study aimed to investigate whether the addition of LPND to total mesorectal excision (TME) confers survival benefits in rectal cancer patients with clinical lateral pelvic node metastasis (LPNM). Methods From January 2015 to January 2021, a total of 141 rectal cancer patients with clinical evidence of LPNM who underwent TME + LPND were retrospectively analysed and divided into the LPNM group (n = 29) and the non-LPNM group (n = 112). The LPNM group was further subdivided into a high-risk LPNM group (n = 14) and a low-risk LPNM group (n = 15). Propensity score matching (PSM) was performed to minimize selection bias. The primary outcomes of this study were 3-year overall survival (OS) and disease-free survival (DFS). Results Of the 141 patients undergoing LPND, the local recurrence rate of patients with LPNM was significantly higher than that of patients without LPNM both before (27.6% vs. 4.5%, P = 0.001) and after (27.6% vs. 3.4%, P = 0.025) PSM. Multivariate analysis revealed that LPNM was an independent risk factor for not only OS (HR: 3.06; 95% CI, 1.15–8.17; P = 0.025) but also DFS (HR: 2.39; 95% CI, 1.18–4.87; P = 0.016) in patients with LPNM after TME + LPND. When the LPNM group was further subdivided, multivariate logistic regression analysis showed that OS and DFS were significantly better in the low-risk group (obturator/internal iliac artery region and < 2 positive LPNs). Conclusion Even after LPND, LPNM patients have a poor prognosis. Moreover, LPNM is an independent poor prognostic factor affecting OS and DFS after TME + LPND. However, LPND appears to confer survival benefits to specific patients with single LPN involvement in the obturator region or internal iliac vessel region. Furthermore, LPND may have no indication in stage IV patients and should be selected carefully.